Thermopylae threefold - Olędzki, Marek; Waszak, Damian (Armia kontra natura, 2020)
Thermopylae, situated in Greece, was a special place created by Nature, which played an important and incomparable role in the times of the history of the antique wars. The place formed a specific ‘eye of the needle’ which impeded all types of invaders to get into the Middle and Southern Greece, that is to the most politically and economically important centres. It was determined by its land formation of a narrow passage between the steep Kallidromos mountains and the seaside or, more accurately the Malian Gulf. The geomorphological studies of Greek scientists made this situation even more precise by proving that next to the steep mountains there was an extensive swamp, made by warm sulphur springs beating above. It was this swamp, therefore, that made the passage through Thermopylae even narrower, approximately about several dozen metres wide (Fig. 2). This place is the result of the reconstruction as the current situation (Fig. 1) does not resemble of the landform of the antique times. The fundamental change was caused by the accumulative activity of the nearby Spercheios river ‘pushing aside’ the bank of the Gulf by a few metres as well as by the change of the previous swamp into the travertine rock present today. The authors of the paper analyse three big military conflicts in Thermopylae, which took place in the three memorable years that is: 480, 279 and 191 BC. The selection criterion was the epoch when they happened, that is the antique, as well as the active background of the nature of the location, which remained unchanged in the discussed times. In addition, all three described conflicts, strictly connected with the geomorphological determinants of Thermopylae, found their course with far-reaching similarities. The first part discusses the Xerxes’ army invasion of Greece in 480 BC and the heroism of the 300 led by Leonidas. As is widely known, this battle has already been properly recognized in the literature on the subject. The original contribution of the authors is taking into consideration the newly discovered geomorphological determinants of Thermopylae, mentioned above. This applies to a significant degree the other two conflicts discussed in the article, newly interpreted by the authors, that is the invasion of Brennus with the Celtic hordes intending to settle in the Hellas (279 BC) and unfortunate battles of Antiochus III with the Romans in 191 BC.